The influence of atopic dermatitis on children's lives (Research, Society and Development, 2020)
Atopic dermatitis influences the psychological, neurological and social spheres, involving the patient, family and school because it generates symptoms that interfere negatively in the child's life. Objective: to identify the influence of atopic dermatitis on the child's life. Methodology: the searches were carried out in two bibliographic databases - PubMed and Scielo. Articles written in English and Portuguese, published from January 1985 to December 2016, were selected, related to: atopic dermatitis in the age group from 0 to 16 years. Results: children with atopic dermatitis develop less general daily activities than children without the pathology, as well as, have difficulty being alone, cry excessively, are more nervous, irritated, unhappy, more worried, insecure and have low self -esteem. Research has shown that the number of children who reported sleep interference is high and that the prevalence of attention deficit disorder, hyperactivity, anxiety, depression, conduct disorders and autism has been significantly increasing in children with atopic dermatitis. Conclusions: atopic dermatitis is a socially and psychologically relevant dermatosis, involving the patient, family and school in factors that, if not worked properly, generate considerable future consequences in the neurological, psychological and social spheres, harming the child's well-being and development.